DAMPAK POLA ASUH OTORITER TERHADAP PERILAKU AGRESIF ANAK DI TK BINA INSANI PASIR TANGKIL LEBAK - Siti Erma Maemunah (LPPM Universitas Bina Bangsa, 2024)
Authoritative parenting can make children feel pressured, constrained and less independent, thus forming a negative self-concept and triggering deviant behavior, one of which is aggressive behavior. This research was conducted to examine the effect of authoritative parenting on aggressive behavior in children aged 5-6 years at Bina Insani Kindergarten Pasir Tangkil Lebak. The research population was parents who had children aged 5-6 years at the Bina Insani Pasir Tangkil Lebak Kindergarten. Using a purposive sampling method, 65 parents who practiced authoritative parenting were selected from 136 questionnaires distributed directly. Questionnaires are used to collect data. Data were analyzed using a linear regression test using the SPSS program. The results of the research show that the authoritative parenting style variable has a positive and significant effect on the aggressive behavior of children aged 5-6 years. The results of data analysis show the equation Y= 5.372 + 0.578 X. Authoritative parenting influences 68% of aggressive behavior. Based on the research results, it is hoped that parents can avoid authoritarian parenting models in order to reduce aggressive behavior in children